Hepatoprotective Role of AV/LCP/18 In CCl4 Induced FLKS Syndrome in Commercial Broilers - Sonkusale, P. M.; lnglepatil , Pratik N.; Jamadade , Siddharth V. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
A total of 75 day old broiler chicks were divided into three equal groups. Group A served as negative  control. Group B (positive control) and C (treatment group) were intoxicated with oral administration  of CCl4 @ 1 ml/kg body weight after every 3rd day during 15-28 days of age. Group C was given  AV/LCP/18 @ 0.10 ml / chick / day in drinking water during 29th-42nd day of age. At the end of  experiment, significantly (P
Keywords: CCl4 toxicity; AV/LCP/18; Hepato-protective; Broilers